Pelatihan Tentang Kandang Maggot yang Terintegrasi dengan Kandang Unggas ke Peternak Unggas di Kota Padang - Resti Rahayu; Robby Jannatan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
The maggot of Black Soldier Fly (BSF) is an alternative protein substitute in poultry feed. Growing maggot is an easy activity and valuable in the bioconversion of household organic waste. Maggot farming cages can be integrated with poultry cages. The integrated cages between maggots and poultry will save space and operational costs. Therefore, the workshop about integrated cage between maggot and poultry was urgently needed for poultry farmers in Padang, West Sumatra. The workshop delivered theory and direct practice of making integrated cages with community partners. The activity was held from October to November 2021 for poultry farmers in Koto Panjang Limau Manis village, Pauh District, Padang. Integrated cages are a solution for poultry farmers interested in maggot cultivation as an alternative feed for their poultry. Partners need support from universities in transferring science and technology because the integration cage is the first time implemented in Kota Padang. In addition, government support is also needed in regulating waste sorting and processing so that the community's organic waste can be converted to valuable products using maggot.